Low-Noise Dual-Way Magnetron Power-Combining System Using an Asymmetric H-Plane Tee and Closed-Loop Phase Compensation - Chen, Xiaojie; Yang, Bo; Shinohara, Naoki; Liu, Changjun (IEEE transactions on microwave theory and techniques, 2021)
To meet the increasing power demands of microwave industries and scientific innovations, a dual-way magnetron (MGT) power-combining system based on an asymmetric H-plane tee combined with closed-loop phase compensation (CLPC) was developed and tested. Only one external injection was used, which could lock both frequencies of the two MGTs via the port coupling of the asymmetric H-plane tee. Additionally, phase control was achieved simultaneously in both MGTs. By tuning the external frequency, the frequencies of both MGTs could be shifted to optimize the power-combining efficiency. The optimal combining efficiency was 95.7%. By adjusting the phase of the external injection, the phase for the combining output was adjusted with a control scope in the 0°-360° range. The phase noise level of the combined output was largely inhibited by implementing only one closed-loop phase compensation subsystem. The phase jitter was limited to approximately ±0.5°, and spur suppression ratios of −61.0 dBc/Hz at 10 Hz, −80.9 dBc/Hz at 100 Hz, −91.6 dBc/Hz at 1 kHz, and so on were achieved. Moreover, we deduced the corresponding power-combining theories in the asymmetric H-plane tee and noise reduction using the closed-loop compensation method. The numerical predictions qualitatively agreed with the experimental results. Additionally, this research reveals that the proposed techniques have great potential for future power-combining systems because they provide higher power output and noise reduction.